DEVELOPMENT OF MOTION ANALYSIS IN CROWDED SCENES FOR REAL TIME VIDEO SURVEILLANCE - ABAS, NUR AFIQAH (IRC, 2019)
The purpose of this project is to detect crowded scene. This is because, most of the time, when there is a crowd forming, it means that something significant is happening such as someone having a heart attack, there is an event like concert, someone has been robbed and more. When crowd can be detected in real time from video surveillance, the person behind the monitor can take necessary precaution and call any emergency line if needed. In this project, Matlab software were used for the development of algorithm to detect crowd as well as motion detection. However, the result is not as accurate yet and will be improved in the future. With this project, hopefully it can be implemented in a lot of CCTV in the future as it will be very helpful for the person who monitors the viewpoint of the CCTV to detect any dangerous threat that happens in a crowd easily.